Accessibility and Usability of Social Network for Career Guidiance Among Secondary School Student of Ilorin Metropolis - Ehindero , Elizabeth Ronke; Bolaji , Hameed Olamilekan; Abdulkareem , Habibat Bolanle (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research investigates the evolving nature of career guidance, analyzing the impact of social networks on students' exposure to diverse career opportunities and information sources. It underscores the shift from traditional, limited career information sources within schools and immediate environments to the vast array of resources available through social networking platforms. The study employs a comprehensive analysis of survey data, exploring respondents' perceptions and acceptance levels regarding the utilization of social networks for career guidance. Statistical analysis reveals an insignificant relationship between social network usage and career guidance among secondary students, prompting a deeper understanding of the complexities surrounding the efficacy of these platforms in guiding career decisions. It was recommended that advocate for enhancing online career guidance resources, fostering collaboration among stakeholders, strengthening digital literacy programs, bridging gaps between social networks and formal career guidance, and encouraging continued research to comprehend the dynamic relationship between social networks and career choices among secondary students.